(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Over the past few decades, wireless mobile communications has expanded significantly. The use of wireless networks and communication in daily life has expanded, and as a result, society is now much more vulnerable to attacks and activities related to cyber security. This study gives a brief introduction of security challenges, such as attacks, loopholes, and challenges in wireless networks, to serve as a foundation for a more in-depth discussion on security techniques and attacks in this difficult environment. Based on the review, it is possible to draw the conclusion that further work in this area should focus on thoroughly examining security issues in all network systems that have been discussed and classifying them uniformly according to where they occur, the type of damage they cause, the network level at which they take place, and the extent of breach of security, etc., along with a characterization of the proposed classes.